Political Ideology, Quality at Entry and the Success of Economic Reform Programs - Smets, Lodewijk; Knack, Stephen; Molenaers, Nadia (World Bank, Washington, DC, 2012)
This study investigates how government ideology matters for the success of World Bank economic policy loans, which typically support market-liberalizing reforms. A simple model predicts that World Bank staff will invest more effort in designing an economic policy loan when faced with a left-wing government. Empirically, estimates from a Heckman selection model show that the quality at entry of an economic policy loan is significantly higher for governments with a left-wing party orientation. This result is robust to changes in the sample, alternative measures of ideology, different estimation techniques and the inclusion of additional control variables. Next, robust findings from estimating a recursive triangular system of equations indicate that leftist governments comply more fully with loan agreements. Results also suggest that World Bank resources are more productive -- in terms of reform success -- in the design of policy operations than in their supervision. Anecdotal evidence from several country cases is consistent with the finding that left-wing governments receive higher quality loans.